Coopera????o tecnol??gica: um estudo das pr??ticas de ecoinova????o nas agroind??strias paranaenses processadoras de mandioca - Cunico, Eliane (2013)
Brazil has one of the bases of its economy agribusiness, represented by agribusiness segment accounted for 22 % of GDP generated in the country in 2012. The generation of wealth, underpinned by productive activities of agro-industries, generates waste and consumes natural resources, greatly interfering in the environmental pillar of sustainability. The central objective of this study is to investigate whether the processing plants cassava generate eco-innovations through technological cooperation, and degree of participation of each university officials, business and government in these interactions. The method used is qualitative - quantitative. The qualitative fragment drew on interviews and content analysis through Atlas.ti tool. For quantitative analysis, questionnaires as a tool for data collection were used. For statistical analysis, we used the software SmartPLS. The main results obtained in this research refers to the development of a model , by means of structural equation modeling to analyze the relationship between technological cooperation and generation of eco-innovation , proving the direct relationship of 33 % of incremental eco-innovation promoted through aspects of cooperation. In addition, an overview of results on the current technological and environmental situation of the segment analyzed and some suggestions for obstacles and difficulties encountered in technological cooperation projects, such as that based the research in question.